PHOTOVOLTAIC MODULE TEMPERATURE ESTIMATION MODEL FOR THE ONE-TIME-POINT DAILY ESTIMATION METHOD - Wong, Kinfatt; Ahmad, Robiah; Abdul Kadir, Kushsairy; Ahmad, Norulhusna (IIUM Engineering Journal, 2024)
Based on the hourly solar radiation and ambient temperature, the hourly power estimation work is carried out using the conventional photovoltaic output power (PVOP) estimation model which is used in conjunction with the conventional photovoltaic module temperature (PVMT) estimation model. These hourly data must be processed further before they can be applied to the daily power estimation work. This estimation work is carried out using conventional estimation methods, which are the multiple estimation processes that are complex, time-consuming, and error prone. Therefore, to avoid these shortcomings, one estimation process is designed and used for daily power estimation work. However, this process produces an incorrect daily output power value due to an invalid module temperature value. Thus, a new PVMT estimation model is developed to solve the problem of the invalid value based on a simple linear regression analysis. The performance of the new model has been validated, giving a Normalized Root Mean Squared Error (NRMSE) value of 0.0215 and a Coefficient of Determination (R2) value of 0.9862. The correct daily output power value is produced with a valid module temperature value, giving a NRMSE value of 0.0034 and a R2 value of 0.9999. These results demonstrate the new model’s applicability and makes the one estimation process accurate, easy, user-friendly, instantaneous, and direct in daily power estimation work. ABSTRAK: Berdasarkan sinaran matahari dan suhu persekitaran per jam, kerja-kerja anggaran kuasa setiap jam dijalankan menggunakan model anggaran kuasa dari dapatan fotovolta konvensional (PVOP) yang digunakan bersempena dengan model anggaran suhu modul fotovolta konvensional (PVMT). Data per jam ini perlu diproses dengan lebih lanjut sebelum ia boleh digunakan pada kerja anggaran kuasa harian. Kerja-kerja penganggaran ini dijalankan menggunakan kaedah penganggaran konvensional, iaitu proses penganggaran berganda yang kompleks, memakan masa dan mudah ralat. Oleh itu, bagi mengelakkan kekurangan ini, satu proses anggaran direka bentuk dan diguna bagi kerja anggaran kuasa harian. Namun, proses ini menghasilkan nilai dapatan kuasa harian yang salah disebabkan oleh nilai suhu modul tidak sah. Oleh itu, model anggaran PVMT baharu telah dibina bagi menyelesaikan masalah nilai tidak sah berdasarkan analisis mudah regresi linear. Prestasi model baharu telah disahkan, memberi nilai Ralat Punca Min Kuasa Dua Ternormal (NRMSE) sebanyak 0.0215 dan nilai Pekali Penentuan (R2) sebanyak 0.9862. Nilai dapatan kuasa harian yang betul dihasilkan dengan nilai suhu modul yang sah, iaitu nilai NRMSE 0.0034 dan R2 0.9999. Dapatan ini menunjukkan bahawa kebolehgunaan model baharu menjadikan proses anggaran lebih tepat, mudah, mesra pengguna, serta-merta dan terus dalam kerja anggaran kuasa harian.